Alteraciones del desarrollo cognitivo y su incidencia en el bajo rendimiento académico en niños entre 6 y 8 años - Maruri Montalván, Mildred Samantha (2021)
This research was developed under the general theme: Alterations in cognitive development and their incidence in low academic performance in children between 6 and 8 years old; offering a characterization of the determining factors that affect academic performance favoring early detection and intervention. The study context was the Community Attention Center of the School of Medical Technology of the University of Guayaquil, where children with low academic performance referred to this center were chosen as a sample for presenting alterations in cognitive development not associated with disability. The purpose of this study is to reduce alterations in cognitive development, favoring academic performance, for which the following research techniques were used: behavioral observation guide, interview and evaluation of the cognitive component using the Loewestein Occupational Therapy Cognitive Scale for children (DOTCA-CH); the latter was applied in order to analyze the areas of greatest difficulty, considering five categories that are orientation, spatial perception, praxis, visual-motor construction and operational processing; All of these processes are necessary for optimal learning, which is why they affect academic performance......